Validation of Body Rocket on-bike wind-tunnel technology: Drag measurement accuracy and aerodynamic gains sensitivity - DeGolier, E.; Cibinel, A.; Barnes, C. (Journal of Science and Cycling, 2024)
While body aerodynamics plays a major role in cycling performance, athletes can only measure their coefficient of aerodynamic drag (CdA) in wind tunnel sessions, i.e. far from actual racing conditions, or via methods that can infer CdA, but do not actually measure all the components of CdA. We present a novel device (Body Rocket) that, by using the same load cell technology as a wind tunnel, directly measures and displays in real time the drag force due to a rider`s body only. We compare drag force measurements carried out simultaneously on a wind tunnel balance and the BR device. On average, the Body Rocket system agrees within 2.3% with the wind tunnel data, under different wind speed, yaw angles and body positions, and reliably detects aerodynamics gains due to positional/equipment changes. As a byproduct of its design, it also enables monitoring of cycling positions, providing valuable feedback otherwise not available to the athlete.